6m-6=8m+8-m

Simple and best practice solution for 6m-6=8m+8-m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6m-6=8m+8-m equation:


Simplifying
6m + -6 = 8m + 8 + -1m

Reorder the terms:
-6 + 6m = 8m + 8 + -1m

Reorder the terms:
-6 + 6m = 8 + 8m + -1m

Combine like terms: 8m + -1m = 7m
-6 + 6m = 8 + 7m

Solving
-6 + 6m = 8 + 7m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-7m' to each side of the equation.
-6 + 6m + -7m = 8 + 7m + -7m

Combine like terms: 6m + -7m = -1m
-6 + -1m = 8 + 7m + -7m

Combine like terms: 7m + -7m = 0
-6 + -1m = 8 + 0
-6 + -1m = 8

Add '6' to each side of the equation.
-6 + 6 + -1m = 8 + 6

Combine like terms: -6 + 6 = 0
0 + -1m = 8 + 6
-1m = 8 + 6

Combine like terms: 8 + 6 = 14
-1m = 14

Divide each side by '-1'.
m = -14

Simplifying
m = -14

See similar equations:

| (x-3)(x-2)=7x+30 | | -24=5t+35 | | 2(15r+5)+17=7(7r-18) | | 5w+6-w=7w-2(w-3) | | x/22+7=10 | | cos(2x)=sin(4x) | | 24x-x^2=144 | | (x^2+x+6)-(8x-2x)= | | 1/3x^2-1/2x-1/3 | | 1/3x-4/6=7/3 | | -70/-35= | | 3x=7x+1 | | 9(-4)-3y=6(y-6) | | 24+8*2*12= | | 8/(x^2-1)=0 | | -(8n+4)=4n-2(6n+2) | | 5y=7xl | | 5-1m=13 | | -5(1-3x)+3x=-4x+5(5x+2) | | 62+(-5)= | | (31/-4)+(-5/8) | | 4x-4(1+3x)=-(1+5x) | | -5(-8X+2)=26+4X | | 8x+17=22 | | t-3t-7=4t-7 | | 5/6+c=1/3 | | 3(x-5)=7x | | 2x^3+x^2-37x-36=0 | | 5t+12=4-3t | | 3x(x+12)+2x(2x+4)=360 | | x^3+47x-35= | | 2(250-x)+x*4=600 |

Equations solver categories